ANAFERON - THE DRUG OF CHOICE IN THE PEDIATRIC POPULATION - O. V. Shamsheva; E. V. Novosad (LLC "Diagnostics and Vaccines", 2015)
Anaferon - antiviral drug with immunomodulating activity. Longstanding experience proved its efficacy and safety in the treatment and prophylaxis of a wide spectrum of viral and bacterial infections in children. The key mechanisms of anaferon action are selective induction of interferons I and II types production and allosteric modulation of interferon-gamma receptor. Excellent safety profile, possibility of its combination with other medicines, absence of self-tapering have made it a drug of choice for the treatment and prophylaxis of various infections of different aetiology.